An elbow exoskeleton for haptic feedback made with a direct drive hobby motor. (October 2020) - Kim, Hubert; Asbeck, Alan T.
Graphical abstract: Abstract: A direct drive motor is one of the simplest mechanisms that can be used to move a mechanical joint. In particular, a brushless direct current (BLDC) motor with no gearing produces a low parasitic torque due to its backdrivability and low inertia, which is ideal for some applications such as wearable systems. While capable of operating with a higher power density than brushed motors, BLDC motors require accurate position feedback to be controlled via vector control at slow speeds. The MotorWare ™ library from Texas Instruments (TI), which is designed to run with a C2000 microcontroller, is written to run BLDCs. However, the code was written to run the motor continuously with an incremental encoder and requires further engineering to be used at low speeds such as in an exoskeleton. In this paper, we present the design of an elbow exoskeleton that can be used for haptic feedback. We provide instructions to build the exoskeleton hardware, custom code to modify software provided by TI so that a motor can provide a controlled torque at low speeds, code to enable the microcontroller to communicate with a computer for high-level commands and data storage, and also provide an overview of how alternate motors could be used with this software setup.